International Study of Objectively-measured Physical Activity and Sedentary Time With Body Mass Index and Obesity: IPEN Adult Study - Van Dyck, D; Cerin, E; De Bourdeaudhuij, I; Hinckson, E; Reis, RS; Davey, R; Sarmiento, OL; Mitas, J; Troelsen, J; MacFarlane, D; Salvo, D; Aguinaga-Ontoso, I; et al. (Springer Nature, 2014)
Background:Physical activity (PA) has been consistently implicated in the etiology of obesity, while recent evidence on the importance of sedentary time remains inconsistent. Understanding of dose-response associations of PA and sedentary time with overweight and obesity in adults can be improved with large-scale studies using objective measures of PA and sedentary time. The purpose of this study was to examine the strength, direction and shape of dose-response associations of accelerometer-based PA and sedentary time with BMI and weight status in 10 countries, and the moderating effects of study site and gender.Methods:Data from the International Physical activity and the Environment Network (IPEN) Adult study were used. IPEN Adult is an observational multi-country cross-sectional study, and 12 sites in 10 countries are included. Participants wore an accelerometer for seven consecutive days, completed a socio-demographic questionnaire and reported height and weight. In total, 5712 adults (18-65 years) were included in the analyses. Generalized additive mixed models, conducted in R, were used to estimate the strength and shape of the associations.Results:A curvilinear relationship of accelerometer-based moderate-to-vigorous PA and total counts/minute with BMI and the probability of being overweight/obese was identified. The associations were negative, but weakened at higher levels of moderate-to-vigorous PA (>50 min/day) and higher counts/minute. No associations between sedentary time and weight outcomes were found. Complex site- and gender-specific findings were revealed for BMI, but not for weight status.Conclusions:Based on these results, the current Institute of Medicine recommendation of 60 minutes/day of moderate-to-vigorous PA to prevent weight gain in normal-weight adults was supported. No relationship between sedentary time and the weight outcomes was present, calling for further examination. If moderator findings are confirmed, the relationship between PA and BMI may be country- and gender-dependent, which could have important implications for country-specific health guidelines.International Journal of Obesity accepted article preview online, 02 July 2014; doi:10.1038/ijo.2014.115.
Keywords: Obesity; Accelerometers; Exercise; Sitting